Diagnostic evaluation of patients with suspected haemophagocytic lymphohistiocytosis. (4th December 2012) - Lehmberg, Kai; Ehl, Stephan
Summary Haemophagocytic lymphohistiocytosis (HLH) is a life‐threatening hyperinflammatory syndrome characterized by severely disturbed immune homeostasis. It can affect all age groups. Diagnostic evaluation of the patient with suspected HLH has to address three main questions: (i) does the patient have HLH? There is no simple diagnostic test, but a number of clinical and laboratory criteria define this clinical syndrome. (ii) Can a trigger be identified? A variety of infections, malignant or autoimmune diseases can contribute to the disturbed immune homeostasis with important consequences for treatment. (iii) Does the patient suffer from a genetic disease predisposing to HLH? Recent advances in the understanding of the genetic and pathophysiological basis of HLH have enabled a better and more rapid answer to this question, which is relevant for prognosis and the decision to perform haematopoietic stem cell transplantation. This review summarizes the current diagnostic approach to the patient with HLH.